Stres Memperlambat Penyembuhan Luka Paska Seksio Sesarea - Ah. Yusuf; Ni Ketut Alit Armini; Arina Nurfianti (Universitas Airlangga, 2007)
Introduction: Decision for cesarean section may lead to the stress for women in delivery. Stress response requires longer recovery time in post cesarean section patients. Most of patients who experience stress before and after surgical is associated with wound healing delay. When this condition continues, the wound will have a higher risk of infection. The objective of this study was to analyze correlation between stress and wound healing phase in post cesarean section patients. Method: A cross sectional design was used in this study. The population were women with cesarean section, both elective or emergency, in Delivery Room I RSU Dr. Soetomo Surabaya. Samples were recruited by using purposive sampling, with 28 samples who met to the inclusion criterias. The observed variables were stress and wound healing phase in post cesarean section patient. Stress data were collected by interview and wound healing measurement done by observation on the 3rd day post cesarean section. Result: The result showed that women with stress experience wound healing delay. The characteristic of wound healing delay was prolonged on inflammation phase, nevertheless there was presence of granulation tissue. Spearman’s rho correlation showed that correlation value r=0.675 with p=0.000. Discussion: It can be concluded that there was strong significant correlation between stress and wound healing phase in post cesarean section patients. It is important to give this information to the patients with cesarean section in order to prevent stress and delay in wound healing phase.